Simultaneous determination of nortriptyline hydrochloride and fluphenazine hydrochloride in microgram quantities from low dosage forms by liquid chromatographyâUV detection - Safwan Ashour; Nuha Kattan (Elsevier, 2012)
A novel method for the simultaneous high-performance liquid chromatographic determination of nortriptyline hydrochloride and fluphenazine hydrochloride was developed and validated. Fluvastatin sodium was used as internal standard. The determination was performed on a Hypersil Gold C8 column (250 mm Ã 4.6 mm i.d., 5Â Î¼m particle size) at 25Â Â°C; the mobile phase, consisting of a mixture of formic acid (0.1Â M, pH 2.16)-methanol (33:67, v/v), was delivered at a flow rate of 1.1Â mL/min and detector wavelength at 251Â nm. The retention time of nortriptyline, fluphenazine and fluvastatin was found to be 5.11, 8.05 and 11.38Â min, respectively. Linearity ranges were 5.0â1350.0 and 10.0â1350.0Â Î¼g/mL with limit of detection values of 0.72 and 0.31Â Î¼g/mL, for nortriptyline and fluphenazine, respectively. Results of assay and recovery studies were statistically evaluated for its accuracy and precision. Correlation coefficients (r2) of the regression equations were greater than 0.999 in all cases. According to the validation results, the proposed method was found to be specific, accurate, precise and could be applied to the simultaneous quantitative analysis of nortriptyline and fluphenazine. Keywords: Nortriptyline hydrochloride, Fluphenazine hydrochloride, Liquid chromatography, Pharmaceutical dosage form